The research of Turkic eposes on oriental motives - Aлжaнбaевa, У. Т.; Сaрсен, Ш. М. (Journal of Oriental Studies, 2018)
The article discusses the research of Turkic eposes on oriental motives by domestic and foreign scientists. Also discusses the chronology of publishing and the authors called «kitabi akyndar».